Investigation of Vitamin D Receptor Gene Polymorphism in Pediatric Patients with Brain Cancer - KOÇ, AHMET; TOKUÇ, AYŞE GÜLNUR (THIEME MEDICAL PUBL INC, 2017)
Aim: In recent years, it is believed that Vitamin D may play a protective role in some cancer types. Certain regions of the Vitamin D receptor (VDR) gene may show a genetic difference in structure. The most frequent polymorphisms in this gene are in Taq-1, Fok-1, and Bsm-1 regions. Some adult cancer types are associated with VDR gene polymorphism such as; colorectal carcinoma, breast carcinoma, and prostate carcinoma. Reviewing the medical literature, no such study had been done on children so far. Materials and Methods: We investigated the association of the three most common gene polymorphisms (Taq-1, Fok-1, and Bsm-1 regions) in VDR gene in 32 children with brain tumors and forty control healthy volunteers. Results: We could not find any relationship between childhood brain tumors and VDR gene polymorphism in these three regions. Conclusion: The present results suggest that the Taq-1, Fok-1, and Bsm-1 polymorphism in the VDR gene and pediatric brain cancers have no association.
Keywords: Brain cancers; childhood; polymorphism; Vitamin D receptor; 1,25-DIHYDROXYVITAMIN D-3; COLORECTAL-CANCER; CELL-DEATH; PREVENTION; GROWTH; TRANSCRIPTION; INHIBITION; MORTALITY; THERAPY; RISK